Practices Advisory Educational Centers: A Review of the process model - Domingo Segovia, Jesús (Education Policy Analysis Archives, 2005)
The processes of change in schools are complex and personal. Those processes have been discussed in multiple dissertations and experiences. Multiple support models and strategies for consulting on the change process have been developed. And we have learned many lessons about these situations. Abandoning our previous naivety, we should move to the fundamentals: the contents and the process of self-reconstruction. This article analyzes practices in consulting with schools and it presents a critical revision of the process pattern using the following: (1) the process of consulting in the journey to improvement (moments, partial processes and purposes); (2) the process of consulting is not a technology but rather a tool; and (3) it describes the learned lessons, the contradictions and the cautions one must take into consideration in the process of consultation.